2022
DOI: 10.3390/ijerph191710483
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of the Impact of COVID-19 on United States’ Frontline Health Care Workers and the Perceived Impact on Their Family Members

Abstract: Although previous research has documented the mental and physical health impacts that COVID-19 had on frontline health workers in the United States, little is known about how the pandemic affected their families. This study sought to explore the impact COVID-19 had on the individual functioning of frontline health care workers in the USA and the perceived impact it had on their family members during the initial nine months of the pandemic. More specifically, this study sought to explore if and how family roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The stigma experienced by participants in our study is in line with other studies [1,29,30]. For example, American COVID-19 described being refused entrance at a store or the hairdresser and encountering difficulties in conversations because of others "knowing better" about COVID-19 [31]. Indian COVID-19 HCWs nondisclosed their jobs out of fear of stigmatization and felt guilty of exposing their family members to COVID-19 infection [26].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The stigma experienced by participants in our study is in line with other studies [1,29,30]. For example, American COVID-19 described being refused entrance at a store or the hairdresser and encountering difficulties in conversations because of others "knowing better" about COVID-19 [31]. Indian COVID-19 HCWs nondisclosed their jobs out of fear of stigmatization and felt guilty of exposing their family members to COVID-19 infection [26].…”
Section: Discussionsupporting
confidence: 86%
“…We interviewed 32 females and 21 males between the age of 23 and 64 years (on average 31 years). Interviewees from the Philippines were on average 43 years old and thus older compared to the other countries (average ranging from [27][28][29][30][31][32][33]. Interviewees worked as nurse assistants (n = 9), nurses (n = 25), or physicians (n = 18) on COVID-19 departments in urban (n = 45) or rural (n = 3) hospitals.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…These stressors include lockdowns (Westrupp et al, 2021a,b), community infection risks (Fitzpatrick et al, 2020; and relational impacts (Cassinat et al, 2021;Sheen et al, 2021;Wang et al, 2021). Emerging qualitative evidence also support these findings in FHWs, showing that these social stressors have placed significant burden on FHWs during the COVID-19 pandemic (Schaffer et al, 2022;Sheen et al, 2022). These findings, therefore, highlight the need to further our understanding of key predictors of psychological distress and wellbeing amongst FHWs during the COVID-19 pandemic that considers stressors beyond work, such as pandemic and social stressors.…”
Section: Introductionmentioning
confidence: 54%
“…Lee et al [ 70 ] found that greater stress on family and social relationships was a risk factor for psychological distress. The Covid-19 pandemic and infectious disease control measures such as lockdowns have caused psychological distress for health care workers and their families [ 71 ] and also have had a severe impact on the family lives of the subjects [ 72 ].…”
Section: Discussionmentioning
confidence: 99%